Chemical Reaction Engineering I: Manual for Performing Laboratory Exercises - Pečar, Darja (University of Maribor Press, 2025)
Manual for performing laboratory exercises in the course Chemical Reaction Engineering I represents a teaching aid for students to be able to approach experimental work in the laboratory.